Improving air permeability of paper with acrylic and melamine resins. (30th September 2013) - Ma, Jinxia; Zhou, Xiaofan; Zhang, Dan; Xiao, Huining
Abstract A novel approach was developed to fabricate structures with high bulk from curled cellulosic material and to eliminate the pulp loss occurring in conventional mercerising pulp processes. Cellulose fibres treated with acrylic resin and melamine resin were curled as a result of the cross‐linking and solidification of the resins. The curled fibres brought about incompact structures of cellulose fibres with high air permeability of paper. Various influencing factors were investigated to control the air permeability of the substrates, including pulp consistency, resin amount and solidification temperature. The results showed that when the pulps at 30% consistency were treated with 10% (wt. on dry fibre) resin and solidified at 140°C, the resulting paper had similar or even better air permeability than that made from the mercerised pulps.